The Russian Invasion of Ukraine and the Future of Democracy in South Africa (The Strategic Review for Southern Africa, 2022)
The South African government and the ruling African National Congress shared the ambivalent responses of many African countries to the Russian invasion of Ukraine in February 2022. Analysing the South African response to the invasion, in the United Nations General Assembly debate and elsewhere, this paper suggests that the country’s professed “non-alignment” or neutrality was misleading, for South Africa was more critical of Western countries (and Ukraine) than of Russia. The support for an imperially minded, undemocratic Russia cast doubt on South Africa’s commitment to liberal democracy. Statements by government officials and members of civil society after the invasion suggested that liberal democracy was tainted by its association with the West. The future of democracy in South Africa is likely to be further weakened by implicit or explicit alignment in the post-invasion world with Russia against the West, for the West is unlikely to strengthen its commitment to democracy in Africa in the face of the challenges posed by Russia and China, countries that have no interest in democracy. While surveys suggest that a majority of South African citizens want their democratic system to continue, the governing elite’s alignment with Russia is likely to weaken the country’s pro-democratic forces.